An effective back‐off selection technique for reliable beacon reception in VANETs - Shah, Syed Adeel Ali; Ahmed, Ejaz; Ahsan Qureshi, Muhammad; Jan, Sadeeq; MD Noor, Rafidah (International journal of communication systems, 2019)
Summary In safety‐critical scenarios, reliable reception of beacons transmitted by a subject vehicle is critical to avoid vehicle collision. According to the employed contention window sizes in IEEE 802.11p, beacons are transmitted with a small contention window size. As a result, multiple vehicles contend for the shared channel access by selecting the same back‐off slot. This is a perfect recipe for synchronous collisions wherein reliable beacon delivery cannot be guaranteed for any vehicle. We consider the problem of selecting the back‐off slots from the current contention window to provide reliable delivery of beacons transmitted by a subject vehicle to its neighbors. Given a safety scenario, we propose a Pseudo‐Random Number Generator (PRNG)‐inspired back‐off selection (PBS) technique. The proposed technique works on the hypothesis that synchronous collisions of beacons transmitted by a subject vehicle can be reduced if all its neighbors select different back‐off slots (ie, not the back‐off slot selected by the subject vehicle). The discrete‐event simulations demonstrate that PBS can increase the overall message reception from a subject vehicle, in comparison with the uniform random probability back‐off selection in IEEE 802.11p. Synchronous collisions are frequent in VANETs due to the uniform random probability selection of back‐off slots at the MAC layer. This proposal enables vehicles to predict the back‐off slots selected by a subject vehicle (i.e., vehicle most likely to cause an accident). As a result, transmitted beacons from the subject vehicle are received with greater reliability in comparison to the IEEE 802.11p.